2018
DOI: 10.4236/asm.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Dysfunction in Elfayoum Governorate

Abstract: Introduction: female sexual dysfunction (FSD) is a complex and poorly understood condition that affects females of all ages. Female sexual dysfunction has been a cyclic rather than a linear process that emphasizes biologic, psychological, social, hormonal, and environmental factors. Female sexual dysfunction is a high prevalent disorder reaching up to 60% of females with reported higher levels in postmenopausal. Aim of the work: was to estimate prevalence of FSD and its related factors in Elfayoum city. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…A study in El-Fayoum city, Egypt the authors reported that sexual dysfunction occurs in 61.2% of women. [33] In another study done in Egypt, 52.8% of females reported sexual dysfunction. [35] These variations in results between studies done in Egypt may be due to differences in the characteristic of samples studied and methodology used in data collection by researchers.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…A study in El-Fayoum city, Egypt the authors reported that sexual dysfunction occurs in 61.2% of women. [33] In another study done in Egypt, 52.8% of females reported sexual dysfunction. [35] These variations in results between studies done in Egypt may be due to differences in the characteristic of samples studied and methodology used in data collection by researchers.…”
Section: Discussionmentioning
confidence: 96%
“…The research on female sexual dysfunction has gained force in this time because sexual dysfunction is an illness of its entity and is prevalent in all populations. [33,34] In the Arab world, culture proscribes openly discussing sexual issues, and this also relates to Egypt. Sexual problems are not declared likely because women felt shy and refused to mention sexual problems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Basically, the types of women's sexual dysfunction and related factors are less studied in the Middle East. [2930] Besides, Although Elaeagnus angustifolia has been highly recommended to be used in Iranian traditional medicine, but little studies have been conducted in this area up to now. [3132] Therefore, the present study aims to compare the effects of Elaeagnus angustifolia capsule and sildenafil citrate tablet on HSDD in women referring to the selected health centers affiliated to Shiraz University of Medical Sciences, Shiraz, Iran.…”
Section: Introductionmentioning
confidence: 99%